Temperature Non-Uniformity of Ice-Field Surface at Covered Skating-Rinks - P. I. Diachek; D. G. Livansky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
The paper considers design variants and requirements to temperature regime of  an ice field which is used for organization of ice-hockey, figure skating and skating  competitions. The  purpose of the presented paper is to ensure the conditions which make it possible to obtain high sports results owing to preparation of an ice-field with the required characteristics.  A heat-conductivity differential equation  with due account of heat-exchange convective processes on the surface of an ice-field and radiation heat-exchange with surrounding structures has been solved with the help of numerical methods as applied to conditions of the problem.